The Development and Design of an Interactive Digital Training Resource for Personal Tutors - Woods, Kathryn (Frontiers in Education, 2020)
This paper details the development and design of an interactive digital training resource for personal tutors in the Arts Faculty at the University of Warwick in 2018. The Arts Faculty Personal Tutor Training Resource aimed to enhance staff and student experiences of personal tutoring. The training was designed and delivered through the open-source learning design tool H5P within the University of Warwick’s Virtual Learning Environment, Moodle. The training resource contains a mixture of text, images, videos and links to further resources that introduce learners to personal tutoring policy, structures, processes and support, and best personal tutoring practice. The resource also contains interactive activities that enable learners to condense their learning, reflect on their personal tutoring knowledge and practice, and see their progress as they move through the different stages of the training. The resource was designed to be interactive to make the content as engaging as possible for learners and to promote the retention of knowledge. It was also designed with different learners’ levels of digital literacy and accessibility needs in mind. This paper outlines the context of the training’s development, and the pedagogic approaches, methods and principles that informed the learning design. It also provides an account of the design process and a description of the training content. This case study demonstrates the value of online training and resources for supporting personal tutors by showing the positive impact that the Arts Faculty Personal Tutoring Training Resource has on staff and student experiences of personal tutoring at the University of Warwick. It also shows that personal tutors welcome online training and resources, and that online training is often preferred to face-to-face training because it can be used and accessed according to the requirement of the user at any time.